Beam Transmission Properties in High Power Ytterbium-Doped Tandem-Pumping Fiber Amplifier - Ping Yan; Zehui Wang; Xuejiao Wang; Qirong Xiao; Yusheng Huang; Jiading Tian; Dan Li; Mali Gong (IEEE Photonics Journal, 2019)
This paper presented beam evolution in entire fiber laser from a more qualitative perspective. Specifically, the beam transmission properties under the condition of the disturbances of the refraction index, during the full length of active fiber in tandem pumping fiber amplifier were shown. The refractive index change was calculated considering the laser gain and the thermal effect. The simulations confirmed the superiority on beam transmission when employing the tandem-pumping configuration, which indicated that tandem-pumping fiber lasers might have better control on beam quality than direct-pumping fiber lasers for further power scaling. Moreover, to verify the model, we set a 1080-nm tandem-pumping fiber amplifier with an output power of 5.4 kW and the beam quality M 2 was measured to be 2.2. The experimental result implied a rationality of the model.